The Influence of Character Education on Student Behavior at SDN 1 Lambheu: A Literature Review - Elyta Dian (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to examine the influence of character education on student behavior at SDN 1 Lambheu. Character education is a vital component in the development of students' moral values and social skills, which significantly contributes to their overall behavior in school settings. This research employs a literature review methodology, analyzing existing studies and theoretical frameworks related to character education and its impact on student conduct. The findings indicate that effective character education programs can foster positive behavior among students, leading to an improved learning environment. Emphasis on values such as respect, responsibility, and empathy not only enhances individual behavior but also promotes a cohesive school community. The study highlights the importance of integrating character education into the curriculum to cultivate all-rounded students who are not only academically proficient but also socially responsible. Recommendations for future research and practical implications for educators and policymakers are also discussed.